Role of cations in the photovoltaic performance optimization of ternary stannates, MSnO3 (M = Ca, Sr, and Ba) and N2SnO4 (N = Ca, Sr, Ba, and Zn) - Kim, Dong Hoe; Qu, Li; Kim, Dong Wook; Kang, Seok Beom; Park, Ji Sang; Cho, In Sun (Ceramics International, 2023)
Given the tremendous interest in next-generation photoelectric conversion devices, such as tandem solar cells, indoor photoelectric conversion devices, and image sensors, the development of device-specific electron transport materials is essential for achieving high performance. Sn-based semiconductors are one of the edge materials with the potential to satisfy these requirements. In particular, ternary stannate compounds have shown high potential as electron transport electrodes in several impressive studies. However, systematic research on the electronic band structure and chemical bonding characteristics of these materials remains insufficient. In this study, we present the effect of cations on the crystal structure and electronic band structure of ternary stannate compounds, MSnO3 (MSO, M = Ca, Sr, and Ba) and N2SnO4 (N2SO, N = Ca, Sr, Ba, and Zn). Additionally, their potential as electron transport electrodes is verified by application in dye-sensitized solar cells (DSCs). Notably, although BaSnO3 (BSO) and Zn2SnO4 (Z2SO) had inferior dye adsorption properties, they exhibited higher overall performance in DSCs than the other stannate compounds. The origin of the excellent performances of BSO and Z2SO is attributed to their supportive electronic band features, including the lower flat-band potential and conduction band than that of the lowest unoccupied molecular orbital level of N719 dye and excellent charge transport property. This study highlights the decisive impact of the electronic band structure and charge transport ability of stannate compounds on the photoelectric conversion performance and provides design guidelines for developing new charge transport materials.
Keywords: Dye- sensitized solar cells; Electron transport; Electron-transport materials; Electronic band structure; Performance; Performance optimizations; Photoelectric conversion; Photovoltaic performance; Stannates; Tandem solar cells; BaSnO3; Electronic band structure; Solar cells; Stannates; Zn2SnO4